Presuppositions in Descriptive Utterances on Kawula-Gusti of the Song Ingsun as Alternative Learning Materials for Javanese Language in Junior High Schools - Angelica Wahyu Kartika Budiarti; Sugeng Adipitoyo; Ahmad Rizky Wahyudi (UIN Salatiga, 2026)
Presupposition in descriptive utterances functions as an effective linguistic strategy for subtly instilling philosophical and theological assumptions, as manifested in the contemporary song